Matière de Fès : littérature, cinérgie et cinécriture - Abdelkrim Chiguer (Itinéraires)
Walled up because of an overused binarism, intra-muros vs extra-muros, ordre vs chaos, the medina appears in Aya dans les villes, a collection of short stories, material made of stones, letters, but as well still and animated images. The medina allows to raise an hypothesis: poetics are linked less to architecture, painting, ut picture poesis, than to a wise organization of time, and to movie-making. Fes urbanity displays itself like a form of hybridism, which fragments of time, left over for a while, hold out against any definitive reproduction.